Padrão de Esterases durante o desenvolvimento pós-embrionário de Melipona scutellaris (Hymenoptera, Apidae, Meliponinae) - Rezende, Syomara Hakiko Matusita Soares de (1997)
In the present study, the electrophoretic pattern of the esterases that occur in M. scutellaris, during development post-embryonic ontogenetic, using the gel electrophoresis technique polyacrylamide (non-denaturing PAGE). The esterase profile was shown as follows: - A total of ten regions with sterasic activity, considering the various stages of development. - The variations that occur in the activity of the esterases, in the stages, allowed to enumerate seven sterasic phenotypes for the thirteen stages of analyzed: 1- L1 and L2 larvae phenotype, 2- L3 larva, 3- pre-defecating larva (LPD) phenotype, 4- larva phenotype defecating (LD), 5- pupae phenotype (POB to PPP), 6- bee phenotype nascent (AN) and 7- adult phenotype (A). - The LPD stage was the one with the highest number of bands with sterasic activity. - AS EST11 and EST-2 occur only in larva and adult stages and may be related to circulating HJ metabolism. - Two sterasic bands, EST-7 and EST-8, showed activity only in the larval phases and for this reason, they were considered larva-specific. - In the pupal phase, two bands are identified, EST-5 and EST-6, specific to this phase, which we suggest are related to maturation and reproductive apparatus. The EST-10 band, which extends from LPD to adults can also be associated with maturation and reproductive organs. - Three sterasic regions, EST-3, EST-4 and EST-9 are not characterized as stage-specific, they can appear throughout the development, indicating that they are associated with the metabolism of constitutive gene products. A preliminary analysis of the steric profile of individuals treated and not treated with HJI in order to verify if differences occur in the phenotypic expression of esterases under the effect of Juvenile Hormone, however, there is no change in the sterasic profile of these individuals. The electrophoretic patterns of queens esterases were compared, workers and males of M. scutellaris, it is not possible to characterize sex and caste specific esterases. The fact that we have not been able to associate one or more esterases to the caste determination mechanism in these bees can indicate that these enzymes are not among the main factors determining and / or limiting factors for this differentiation. The study of gene transcription products, throughout development, will enable more accurate analysis.